Decreasing College Enrollment in Nepal: A Comprehensive Examination of Teachers’ Experiences - Chand, Gambhir Bahadur; Joshi, Rajendra Prasad (Exploration अन्वेषण, 2026)
This study investigates the declining trend of student enrollment in higher education institutions in Nepal, a challenge increasingly observed across universities and colleges nationwide. Using a quantitative survey of 40 college-level teachers from Kanchanpur, supported by a focus group discussion with 10 participants, the research explores teachers’ perceptions of the current enrollment situation, identifies the major factors contributing to the decline, and examines the strategies implemented to address the issue. The findings reveal that the primary causes of decreasing enrollment include students’ strong attraction toward foreign education, lack of employment opportunities in Nepal, financial hardship, poor academic motivation, outdated curricula, and ineffective governance in higher education institutions. Quantitative results indicate that over 70% of respondents perceive the current enrollment as declining, with undergraduate programs being the most significantly affected. Qualitative responses further highlight systemic issues such as rigid academic calendars, limited practical and market-oriented courses, inadequate facilities, and poor institutional management. Despite these challenges, institutions have adopted various strategies, including school visits, collaboration with local governments, media campaigns, and efforts to enhance campus environments. The study concludes that revitalising higher education in Nepal requires policy reforms, job-linked academic programs, financial support mechanisms, improved governance, and strengthened institutional capacity. The findings provide critical insights for policymakers, educational leaders, and stakeholders striving to enhance the attractiveness and relevance of higher education in Nepal.